2015
DOI: 10.1590/1983-1447.2015.01.49163
|View full text |Cite
|
Sign up to set email alerts
|

Association between the functional capacity of dependant elderly people and the burden of family caregivers

Abstract: The aim of this study was to characterize dependent elderly people and their main family caregivers and the association between functional capacity of the elderly and the burden of caregivers. This cross-sectional study was conducted with 112 elderly people and caregivers connected to a primary care service in Porto Alegre, Brazil. The applied instruments related to care and socioeconomic variables were Physical and Instrumental Activities of Daily Living (PADL and IADL) and the Burden Interview. The Spearman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0
38

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(73 citation statements)
references
References 10 publications
5
30
0
38
Order By: Relevance
“…Therefore, the prevalence of the female sex is in accordance with the result of other national and international studies (11)(12)(17)(18)(32)(33) . The high average age found was similar to other national studies (14,(34)(35) . However, it was higher than the results of the Canadian study in which researchers found an average age of 48.66 ± 11.16 years (2) .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the prevalence of the female sex is in accordance with the result of other national and international studies (11)(12)(17)(18)(32)(33) . The high average age found was similar to other national studies (14,(34)(35) . However, it was higher than the results of the Canadian study in which researchers found an average age of 48.66 ± 11.16 years (2) .…”
Section: Discussionsupporting
confidence: 91%
“…In this study, most of the children lived with their older parents, while the Canadian research found that only 34.6% of the children lived with their parents (3) . In other Brazilian studies conducted with family caregivers of older adults, most caregivers were daughters who lived with their parents (8,(11)(12)35) . In the Canadian study, considering the three cultural groups of caregiver children, the researchers found scores of Filial Expectation and Duty with overall averages of 20.85 and 25.12, respectively (2) .…”
Section: Discussionmentioning
confidence: 99%
“…A maioria dos cuidadores do presente estudo não trabalhava no momento, assim como averiguado em estudos em que 91,6% e 70,8% dos cuidadores, respectivamente, não possuíam ocupação ou renda fora do lar, o que pode contribuir para a sobrecarga do cuidado (14,15) . Como consequência do cuidado, que é uma tarefa complexa e que exige tempo e dedicação, os cuidadores acabam deixando de lado seu bem-estar e vivem em função da criança (14,16) . A sobrecarga envolve não somente aspectos físicos, mas também psicológicos, familiares, financeiros e sociais.…”
Section: Discussionunclassified
“…This excessive workload imposed to the caregiver may cause functional (7)(8) and psychological impairment resulting from the daily activities, changes in social life, financial burden, coping with depressive symptoms and cognitive changes (9) , dysfunction of roles or interruption of family routine (7) .…”
Section: Introductionmentioning
confidence: 99%